The polarisation of auroral emissions: A tracer of the E region ionospheric currents - Bosse, Léo; Lilensten, Jean; Johnsen, Magnar G.; Gillet, Nicolas; Rochat, Sylvain; Delboulbé, Alain; Curaba, Stephane; Ogawa, Yasunobu; Derverchère, Philippe; Vauclair, Sébastien (Journal of Space Weather and Space Climate, 2022)
International audience It is now established that auroral emissions as measured from the ground are polarised. The question of the information given by this polarisation is still to be explored. This article shows the results of a coordinated campaign between an optical polarimeter and several ground-based instruments, including magnetometers, the EISCAT VHF radar, and complementary luminance meters in the visible domain (Ninox). We show that in the E region, the polarisation is a potential indicator of the ionospheric currents, velocity, and dynamics.